Prediction of Local Infectious and Inflammatory Complications After Reconstructive Surgery of Aorta - Oksana O. Grin; Natalia V. Beloborodova; Marina S. Grekova; Aliсa K. Pautova; Eduard R. Charchyan; Boris A. Akselrod; Olga V. Dymova; Lyubov I. Rizun; Alexander A. Eremenko; Maxim A. Babaev (Общая реаниматология)
Aim. To identify biomarkers for prediction and early diagnosis of infectious and inflammatory complications in patients after aortic surgery.Materials and methods. The study included 57 patients who underwent surgical procedures on the aorta and its branches under cardiopulmonary bypass and myocardial ischemia. The cohort was divided into two groups: patients with an uneventful postoperative period (group 1, N=35) and patients with local infectious and inflammatory complications after surgery (group 2, N=22). Serum levels of procalcitonin (PCT), interleukins (IL-6 and IL-10), and aromatic microbial metabolites (AMM) were measured before surgery, upon admission, and six hours after admission to the ICU. On postoperative days 3 and 6 neutrophil, lymphocyte, and platelet counts were assessed, and neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were calculated.Results. There were no significant differences in sex, age, or comorbidities between groups 1 and 2. Patients in group 2 had a more severe intraoperative period and required a longer ICU stay. Predictive markers of complications included IL-6143.35 pg/mL at ICU admission (sensitivity 42.9%, specificity 90.9%, AUC 0.789, 95% CI 0.669–0.909, P0.001); PCT0.12 ng/mL 6 hours after ICU admission (sensitivity 90.9%, specificity 54.3%, AUC 0.762, 95% CI 0.634–0.891, P0. 001); NLR 7.8 on postoperative day 3 (sensitivity 72.7%, specificity 68.6%, AUC 0.710, 95% CI 0.571–0.850, P=0.003); and AMM (before and after surgery) 0.185 (sensitivity 77.3%, specificity 71.4%, AUC 0.780, 95% CI 0.651–0.909, P0.001).Conclusion. Values of IL-6, PCT, NLR, and AMM reflect different features of the inflammation and can be used for prediction and early diagnosis of infectious and inflammatory complications in cardiac surgery patients.